2021
DOI: 10.5606/tftrd.2021.6690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet-rich plasma injection on pain, range of motion, and disability in adhesive capsulitis: A prospective, randomized-controlled study

Abstract: Objectives: In this study, we aimed to investigate the effectiveness of intra-articular platelet-rich plasma (PRP) injection in adhesive capsulitis. Patients and methods: Between January 2019 and December 2019, a total of 40 patients (21 males, 19 females; mean age: 57.1±6.5 years; range, 44 to 72 years) with idiopathic adhesive capsulitis were included. The patients were randomly assigned into two equal groups as the PRP and the control group. The PRP group received two doses of PRP via intra-articular route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The detailed characteristics of the included studies are shown in Table 1. We included 6 RCTs [15][16][17][18][19][20] and excluded 8 nonrandomized studies. The study inclusion process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed characteristics of the included studies are shown in Table 1. We included 6 RCTs [15][16][17][18][19][20] and excluded 8 nonrandomized studies. The study inclusion process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up duration ranged from 6 to 26 weeks, but more than half of the studies (4/6) reported a 12-week follow-up period. [15][16][17]20 Females constituted around 59.2% (339/573) of the total patient population with gender reported. Age was reported using different methods including range, mean, and median.…”
Section: Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRP can exert an anti-inflammatory effect at the inflammation site by releasing TNF-α, HGF, and lipoxin A4, which are potent anti-inflammatory agents [ 94 , 95 ].…”
Section: Adhesive Capsulitismentioning
confidence: 99%
“…24 Although it is not possible to define a univocal protocol to date, rehabilitation treatments play a pivotal role in the management of FS, and comprise patient education, stretching exercises, joint mobilization, and manual therapy. 4,[25][26][27] Physical modalities such as low-level laser therapy (LLLT), magnetotherapy, ultrasound (US) therapy, and transcutaneous electrical nerve stimulation (TENS) are also commonly used. [28][29][30] Manipulation under anesthesia (MUA) is another possible procedure which involves scapular stabilization with subsequent flexion, extension, abduction, adduction, internal and external rotation of the shoulder until reaching the final degrees of movement following anesthesia.…”
Section: Introductionmentioning
confidence: 99%